A Meta-Analysis and Systematic Review of the Literature to Evaluate Potential Threats to Internal Validity in Probe Procedures for Chained Tasks. (November 2015) - Alexander, Jennifer L.; Smith, Katie A.; Mataras, Theologia; Shepley, Sally B.; Ayres, Kevin M.
The two most frequently used methods for assessing performance on chained tasks are single opportunity probes (SOPs) and multiple opportunity probes (MOPs). Of the two, SOPs may be easier and less time-consuming but can suppress actual performance. In comparison, MOPs can provide more information but present the risk of participants acquiring steps from probing alone. The authors reviewed and summarized 20 years of single-case design literature that evaluated methods of teaching chained tasks to individuals with disabilities. The authors identified a total of 33 studies. Individual tiers of multiple baseline and probe design graphs were analyzed to evaluate possible differences in participant responding within and between baseline and intervention conditions. Differences were evident, but none considered statistical when comparing data from SOPs and MOPs. The authors discuss possible publication bias as a reason for these findings and offer future research ideas to extend the literature on probe procedures.